CRISPR-CAS9 MEDIATED KNOCKOUT OF THE MERTK GENE IN BLADDER CANCER CELL LINES USING DOUBLE CUT DELETION. - Beisekeyeva, Tomiris (Nazarbayev University School of Medicine, 2025)
MERTK is a proto-oncogene with tyrosine kinase activity and is part of the TAM class of receptor tyrosine kinases. The gene MERTK is located on chromosome 2 and encodes a transmembrane protein with two immunoglobulin-like moieties, two fibronectin type-III domains, and one tyrosine kinase domain. MERTK is widely expressed in a diverse array of cells including macrophages, natural killer cells, dendritic cells, platelets and T-cells. Moreover, MERTK expression can be found in oocytes, testis, kidney and urinary bladder. MERTK receptor activation is triggered by interacting with appropriate ligands. The main ligands that activate MERTK are Protein S and GAS6. Normally, MERTK regulates the removal of apoptotic cells and is involved in the process of efferocytosis. During efferocytosis, apoptotic cells are engulfed by phagocytic cells without spreading intracellular content from the apoptotic cells into the extracellular space. This type of apoptotic engulfment is crucial for tissues that are unable to release the content from their dead cells to the environment. Furthermore, MERTK signaling reduces inflammation. GAS6/MERTK signaling has been demonstrated to prevent the production of pro-inflammatory mediators such as TNF-alpha and IL-6. Furthermore, Mer-receptor tyrosine kinase, through stimulating the PI3K/AKT signaling cascade, accelerates M2 polarization of macrophages and contributes to tissue repair and wound healing, and induces cellular proliferation. However, dysregulation in the MERTK can lead to cancer progression, invasion, and migration. Studies have shown that interaction between MERTK with its ligands activates JNK/ERK1/2, beta-catenin, and PI3K/AKT signaling pathways, altogether these signaling activations help cancer cells to proliferate, migrate, invade, and survive. Thus, MERTK has a profound effect on the progression of cancer cells. However, there is limited information about the role of MERTK in the advancement of bladder cancer. This study aims to fill these gaps and reveal the role of MERTK in bladder cancer cell development. This research will investigate the role of MERTK receptor in bladder cancer development. By utilizing a CRISPR/Cas9 genome editing approach, the MERTK gene knockout will be performed in 253J and UM-UC-3 bladder cancer cell lines. This information and knowledge gained in this study could be useful for the further development of therapeutics and personalized medicine for the cure of bladder cancer.
Keywords: MERTK; bladder cancer; cancer signaling; immune response; CRISPR-CAS9; PROS-1; GAS-6; PI3K/AKT; JNK; 253J; UM-UC-3; Type of access: Embargo